Virtual dynamic models as a means of forming professional competences of future engineer-educators - Ігнатенко, Сергій (Pedagogy of Higher and Secondary Education, 2014)
Ignatenko S. V. Virtual dynamic models as a means of forming professional competences of future engineer-educators. The article defines the term “virtual dynamic model” and discusses the didactic possibilities for a virtual dynamic model. The author proves the effectiveness of their use in training future engineer-educators.